A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 12 PEKANBARU IN USING PRESENT PERFECT TENSE - Widya Sri Ramadhani; Atni Prawati; Marzuki ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This descriptive research was aimed to find out the ability of the first year students of SMAN 12 Pekanbaru in using Present Perfect Tense. The research data were collected in July 2016. The subject of this research was class X IPS 1 which consisted of 39 students. The data were collected by giving test to the students in the form of words arrangement and completion of blank spaces in passage. The results of the research showed that the first year students of SMAN 12 Pekanbaru in the use of have/has got the mean score of 67, the use of irregular verb got the mean score of 47.94 and the use of regular verb got the mean score of 53.5. Therefore, it can be concluded that the highest ability of the first year students of SMAN 12 Pekanbaru in using Present Perfect Tense was in the use of have/has.Keywords: Ability, Present Perfect Tense